Seed Vigor Improvement of Red Chili Seeds (Capsicum annuum L.) Using Spirulina platensis as Seed Priming Agent - Samtani, Kariena; Rahmawati, Fitri Ayu; Pratiwi, Indah Wahyu; Atuillah, Nuning; Hidayatullah, Reza Aris; Sabiku, Dewi Fatmawaty; Azizah, Maria; Prasetyo, Hari; Suwardi, Suwardi; Sulistyono, Nantil Bambang Eko; Bintoro, M.; Adnan, Moch. Rosyadi (Agroteknika, 2025)
Red chili is a crucial horticultural crop in Indonesia. The increasing demand for high-quality chili necessitates seeds with optimal germination and growth. Spirulina platensis, a microalgae species, can be cultivated in waste media such as Sugar Mill Effluent (SME). Moreover, Spirulina contains phytohormones that can stimulate seed germination. This study investigated the impact of various concentrations and soaking times of S. platensis solution on red chili seed quality. A factorial Completely Randomized Design (CRD) was employed with 5 levels of microalgae biomass concentration: control (untreated seeds), 0, 30, 45, and 60% and 3 levels of soaking time: 1, 2, and 3 hours. Data analysis involved ANOVA and Bonferroni post-hoc tests at a 5% level using GraphPad Prism version 5.01. The results demonstrated seed priming application using S. platensis significantly enhanced seed vigor. The S. platensis treatment at 60% concentration for 2 hours significantly reduced MGT by 1 day, while 30%-2 hours and 60%-3 hours treatments exhibited the highest germination rate (100%), vigor index (49.17% in 30%-2 hours), seed growth simultaneity (85.56% in 60%-2 hours and 83.33% in 30%-2 hours), and growth rate (11.48% in 60%-3 hours and 11.11% in 30%-2 hours), with the 60%-3 hours treatment showing the longest shoot (2.73 cm) and radicle (8.13 cm) lengths, compared to the control. These findings suggest that S. platensis priming can be a promising approach for improving seed quality and crop establishment.